Extraction Equilibrium of Gallium(III) from Nitric Acid Solutions by Di(2-ethylhexyl)phosphoric Acid Dissolved in Kerosene - Tsai, Hung-Sheng; Tsai, Teh-Hua (Asian Journal of Chemistry, 2012)
The solvent extraction of gallium(III) from aqueous nitric acid medium with di(2-ethylhexyl)phosphoric acid (D2EHPA) dissolved in kerosene at 25 ºC has been studied. The extraction equilibrium data between the organic phase and the aqueous phase were used in the graphical and numerical analysis. The results showed that the stoichiometry of the extraction reaction and the compositions of gallium-D2EHPA complexes in organic phase. The extraction equilibrium constant of GaR3 in the organic phase has been determined. The results of gallium(III) extraction indicated that the distribution ratios increased when either the pH value of the aqueous phase and/or the concentration of D2EHPA in the organic phase increased. Finally, considering gallium and nitrate ions will form complex reactions, the distribution of gallium ions and their complexes were examined.